Efficacy of ezetimibe as monotherapy or combination therapy in hypercholesterolemic patients with and without diabetes - Osame, Keiichiro; Sugiyama, Takehiro; Noda, Mitsuhiko; Takarabe, Daisuke; Kishimoto, Miyako; Okamoto, Masahide (The Journal of Medical Investigation, 2011)
Ezetimibe selectively inhibits dietary and biliary cholesterol absorption and reduces serum cholesterol levels when administered alone (monotherapy) and along with common lipid-regulating agents (combination therapy). To evaluate the effect of ezetimibe therapy on the lipid profile, glucose metabolism, and levels of cholesterol absorption and synthesis markers, we administered 10 mg ezetimibe to 50 hypercholesterolemic patients with or without diabetes. The serum levels of low-density lipoprotein cholesterol and total cholesterol were significantly reduced at 4 and 12 weeks of ezetimibe therapy in diabetic patients of both the monotherapy and combination-therapy groups and in nondiabetic patients of the combination-therapy group. The serum levels of the cholesterol absorption markers were significantly reduced, while those of the cholesterol synthesis markers were significantly increased at 12 weeks of ezetimibe therapy. No significant differences were noted in the values of the parameters of glucose metabolism in all patients. We also investigated the clinical characteristics of patients who exhibited a good response to ezetimibe (ezetimibe responders); however, multivariate regression analysis did not reveal a correlation between ezetimibe efficacy and patient characteristics such as gender, age, BMI, diabetic condition, method of ezetimibe administration, and the initial absolute values of cholesterol absorption/synthesis markers levels. In conclusion, ezetimibe therapy significantly improved the lipid profile without disturbing glucose metabolism. We were unable to identify the specific characteristics of ezetimibe responders among our subjects. However, we may interpret this result as suggesting that ezetimibe can be used in any population to lower low-density lipoprotein cholesterol levels. J. Med. Invest. 58: 86-94, February, 2011